Screening and characterization of sex-specific sequences through 2b-RAD sequencing in American shad (Alosa sapidissima) - Du, Jia; Liu, Qinghua; Zheng, Yuhong (PloS one, 2023)
American shad ( Alosa sapidissima ), introduced from the United States, has become one of the most expensive farmed fish in the aquatic product market of China. The shad reveals significant sexual dimorphism in growth and behaviors. For the study, five male-specific tags were identified in two-generation breeding populations of Alosa sapidissima and were verified by PCR amplification. Averages of 10,245,091 and 8,685,704 raw and enzyme reads were obtained by high-throughput sequencing of the 2b-RAD library, respectively. 301,022 unique tags were obtained from the sequences of twenty samples with sequencing depths of 0 to 500. Finally, 274,324 special tags and 29,327 SNPs were selected with a sequencing depth of 3 to 500. Eleven preliminary screening male-specific tags and three male heterogametic SNP loci were isolated. After verification by PCR amplification, five male-specific sequences of 27 bp located on chromosome 3 were screened out. Chromosome 3 could be assumed to be the sex chromosome of Alosa sapidissima . Sex-specific markers will provide invaluable and systematic animal germplasm resources to allow for the precise identification of neo-males for the all-female breeding of Alosa sapidissima in commercial aquaculture.